2009
DOI: 10.1097/tp.0b013e3181bc419c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Femtosecond Laser-Assisted Corneal Endothelial Keratoplasty: A Randomized Multicenter Clinical Trial

Abstract: FLEK effectively reduces postoperative astigmatism and results in an absence of wound healing related problems in patients with endothelial disease. However, visual acuity is lower as compared with conventional PK, and the high level of endothelial cell loss warrants a modification of the insertion technique of the endothelial graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 48 publications
2
69
0
1
Order By: Relevance
“…25,86 This was attributed to interface haze and increased stray light, potentially caused by laser-activation of keratocytes, as well as irregularity of the laserdissected graft surface. 25 Refinements in graft preparation (manual and automated microkeratome techniques) and progressively thinner lenticules may reduce the role of interface irregularities in determining postoperative visual outcomes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…25,86 This was attributed to interface haze and increased stray light, potentially caused by laser-activation of keratocytes, as well as irregularity of the laserdissected graft surface. 25 Refinements in graft preparation (manual and automated microkeratome techniques) and progressively thinner lenticules may reduce the role of interface irregularities in determining postoperative visual outcomes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…We also included one study that had compared femtosecond laser-assisted endothelial keratoplasty (FLEK) versus PKP. ) was found to be significantly less following EK than PKP, and the endothelial cell counts were significantly lower with EK procedures in another trial (Cheng 2009). In terms of adverse outcomes, Cheng 2009 reported that graft dislocation, acute IOP elevation, primary graft failure and endothelial cell loss were more common in the EK group, whereas wound and suture-related problems were more common in the PKP group.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Detailed characteristics of the included studies are presented in the 'Characteristics of included studies' Cheng 2009 and in an attempt to obtain outcome data for FED eyes alone but they were unable to provide these data. Given the paucity of studies in this area and considering the fact that FED accounted for the majority of the results we included these trials in this review.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations